The Quantity of Money and the Rate of Interest - Smithies, A. (The Review of Economics and Statistics, 1943)
IN THIS paper some of the implications of the approach to the problem of interest in a capitalist economy will be examined. A discussion directed toward interest may seem an anachronism at a time when, in discussion of the recent past, the present, and the future, the determination of the size of the national income has assumed a position of central importance, and instruments for increasing income are available which are admittedly more potent than manipulations of interest rates. But the magnitude of interest rates may have an important bearing on the extent to which private enterprise, and in particular private investment, will occupy the stage in the future. Although conditions are conceivable under which the interest burden of the national debt would not hamper private enterprise, it seems improbable that they will be realized, and I think it can be safely assumed that changes in the interest cost of the national debt will have a significant effect on the rate of private investment. Further, although Dr. Tinbergen I has found that long-term interest rates have had but a moderate effect on investment in the past and have been overshadowed in importance by profit fluctuations in the case of industry and by the shortage and abundance of houses in the case of residential building, it may well be that if a stable national income is achieved in the future, interest rates may be a factor of prime importance in determining the rate of private investment. We need not dwell for long on the question whether interest is a monetary phenomenon in the sense that to assume the absence of money is to assume away one essential determinant of interest. That question has been conclusively answered in the affirmative by the work of Professor Schumpeter and of Lord Keynes.2 Professor Schumpeter has shown that uncertainty is inherent in the process of capitalistic development; that profits are the prizes of the few who plunge successfully into the unknown; and that if the future were certain not only would the genius of the entrepreneur not be required, but existing profits would be encroached upon and finally disappear. Furthermore, in order to exploit their opportunities, entrepreneurs require command over money which enables them to obtain resources for investment either by raiding the current flow of production or by increasing it. Lord Keynes' analysis complements Professor Schumpeter's on the supply side: in order to take advantage of unforeseeable possibilities of profit or to guard against unforeseeable risks, people desire to hold liquid resources, and will surrender them only if they receive sufficient compensation in the form of interest. Since uncertainty is an ever present phenomenonif all else were assumed away, the uncertainty of human mortality 3 would remain liquidity preference is an essential ingredient of any economic situation, and therefore of any valid theory of interest. To assume the absence of money as a store of effectively, uncertainty must be assumed away, since, as Keynes has shown, people will use substitute stores of value if deprived of dollars. And if uncertainty is absent, we are confronted with Schumpeter's compelling argument that, under those conditions, there is no room for the phenomenon of interest. Since interest is a monetary phenomenon in the sense of the last paragraph, it follows that there must be some relation between the rate of interest and the quantity of money, and that, within limits, permanent effects on interest and output can be produced by changes in the quantity of money. The determination of these effects will be the subject of the following sections. Section II will follow the argument of the General Theory, but will, I hope, escape the stigma of vain repetition by suggesting some improvements of Keynes' model and by